Digital Interoperability and the Reconfiguration of Regional Coordination: A Mechanism-Based Perspective from Emerging Platform Economies - Irwan Raharja (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Digital interoperability has emerged as a defining feature of contemporary regional digital economies, yet its role in reshaping cross-border coordination remains under-theorized. While prior research emphasizes regulatory harmonization or platform governance within domestic markets, less attention has been devoted to how interoperable infrastructures reorganize regional coordination in the absence of supranational authority. This article develops a mechanism-based conceptual framework explaining how digital interoperability reconfigures regional institutional alignment in emerging platform economies. Integrating Transaction Cost Economics, ecosystem boundary theory, and regional coordination scholarship, the study identifies four interrelated mechanisms: transaction cost compression, institutional substitution, ecosystem boundary expansion, and coordinated decentralization. Together, these mechanisms demonstrate how infrastructural synchronization can stabilize cross-border exchange without requiring political integration. The framework advances a configurational perspective, arguing that interoperability produces distinct regional outcomes depending on the degree of institutional fragmentation. By reframing interoperability as infrastructural governance rather than technical compatibility, this study contributes to strategy and institutional scholarship and offers a bounded explanation of how digital economies integrate under fragmented governance conditions.